벼 조생 고품질 소득작물 후작 다수성 “만 나” - 고종철(Jong Cheol Ko); 남정권(Jeong Kwon Nam):정진일(Jin Il Choung):하기용(Ki Yong Ha):백만기(Man Gee Baek):김기영(Ki Young Kim); 신운철(Woon Chul Sin):김우재(Woo Jae Kim):이재길(Jae Kil Lee):고재권(Jae Kwon Ko):김보경(Bo Kyeong Kim); 강현중(Hyun Jung Kang):김영두(Young Doo Kim):모영준(Young Jun Mo):김정곤(Chung Kon Kim) (Korean journal of breeding, 2008)
Manna is a new japonica rice cultivar developed from the cross between Iksan438 and Ilmibyeo by the rice breeding team of Department of Rice and Winter Cereal Crop, RDA, in 2005. This cultivar has a short grain shape and about 97 days growth duration from late transplanting to harvesting under Korean climatic conditions. It is resistant to lodging with average 70 cm of culm length. The milled kernels of Manna are translucent with non-glutinous endosperm. It has about 19% amylose content and good palatability of cooked rice compared with Geumobyeo. This cultivar shows resistance to leaf blast and neck blast but susceptibility to bacterial blight and stripe virus diseases. The milled rice yield potential of Manna is about 5.05 MT/ha under the late transplanting cultivation. Manna would be adaptable for the middle and Honam plain of Korea.